PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, KEAMANAN DAN KETERSEDIAAN FITUR TERHADAP MINAT ULANG NASABAH BANK DALAM MENGGUNAKAN INTERNET BANKING (STUDI PADA PROGRAM LAYANAN INTERNET BANKING BRI) - - Ahmad; Bambang Setiyo Pambudi (Universitas Trunojoyo Madura, 2014)
The purpose of this research was to identify variables which influenced re-intention of bank’s customer BRI to re-use Internet Banking BRI either partially or simultaneously.The research used a quantitative method where the populations were all of the BRI customers in the town of Bangkalan who used the Internet Banking BRI services and obtained a sample of 50 respondents its taken using purposive sampling method by distributing questionnaires.